90 Potentiation of T-cell mediated tumor killing via modulation of the fas/fasL pathway. (9th November 2020) - Boiarsky, Jonathan; Upadhyay, Ranjan; Svensson-Arvelund, Judit; Wroblewska, Aleksandra; Bhalla, Sherry; Scholler, Nathalie; Bot, Adrian; Rossi, John; Parekh, Samir; Sadek, Norah; Baccarini, Alessia; Merad, Miriam; et al.
Abstract : Background: T-cell based immunotherapies such as CAR-T, bispecific mAb, transgenic T cells and checkpoint blockade have profound efficacy in multiple tumor types but share a common limitation – target antigen (Ag) escape. 1 2 One approach to address this limitation has been therapy directed at a 'parallel' target (e.g. CD22 after CD19 loss), however, these lineage markers are frequently lost together. 3 Here, we describe an alternate, broadly applicable, approach: potentiating fasL/fas-signaling to increase localized bystander killing of Ag - tumor cells and thereby prevent Ag escape. Methods: We used a CRISPR/Cas9 library to screen for tumor expressed molecules that inhibit or facilitate T-cell killing. We then evaluated one candidate -fas- using murine transgenic T cells, murine and human CAR-T cells, bispecific mAb redirected PBMC, and tumoral RNAseq data from a large CAR-T clinical trial. Results: GFP-specific (JEDI) CD8 T cells were co-cultured with on-target (GFP + ) and bystander (mCherry + ) lymphoma cells that had been transfected with a CRISPR/Cas9 library; this screen revealed several tumor-expressed candidate molecules inhibiting or facilitating T-cell killing. Notably, we observed a marked dependence on fas for on-target tumor killing and then, surprisingly, an exquisite dependence on fas for localized bystander tumor killing. (figure 1 ).Because bystander tumor killing appeared critically fas-dependent, we hypothesized that potentiating fas-signaling might increase bystander killing. An in vitro screen of small molecules that modulate fas-pathway revealed several candidates, including inhibitors of histone deacetylases (HDAC), inhibitors of apoptosis proteins (IAP) and Bcl-2 family members in murine and human systems (figure 2 ). To validate these candidates, we demonstrated that HDACi increased GFP-specific T cell killing of both on-target and bystander lymphoma cells, in a completely fas-dependent manner (figure 3 ). Similarly, using a bispecific antibody-based system, we demonstrated increased, fas-dependent, T cell killing of both on-target and bystander human lymphoma cells with inhibitors of IAP and bcl-2 family members (e.g. MCL1). Conclusions: T-cell mediated tumor killing can be potentiated with fas pathway modulators. This augmentation improves both fas-dependent Ag + and Ag - tumor cell death. Further studies of modulating the fas pathway alongside T-cell based immunotherapies are needed as potential treatments to prevent antigen escape and improve patient outcomes. Acknowledgements: We thank the flow cytometry core facility, microscopy core facility, and the CCMS animal facility at ISMMS. Ethics Approval: The studies were approved by The Mount Sinai Institutional Review Board. References: Zaretsky J, Garcia-Diaz A, Shin D, et al. Mutations Associated with Acquired Resistance to PD-1 Blockade in Melanoma. N Engl J Med 2016: 375(9); 819–20. Majzner R, Mackall C. Tumor antigen escape from CAR T-cell therapy. Cancer Discov 2018;8(10):1219–1226. Jacoby E, Nguyen S, Fountaine T, et al. CD19 CAR immune pressure induces B-precusor acute lymphoblastic leukaemia lineage switch exposing inherent leukaemic plasticity. Nat Commun 2016; 7 :12320.